Effect of Addition of Additive Sikament LN Compressive Strength Of Cement Concrete Using Red and White - Yulfriwini Yulfriwini; Purba R H; Wisman M (International Conference on Engineering and Technology Development (ICETD), 2017)
Various studies and experiments in the field of concrete as part of efforts to improve the quality of concrete. In the construction of high-rise buildings and other massbuilding takes high-strength concrete, normal concrete is the most appropriate choice. Campuaran concrete is usually in the form of sand, gravel, cement and water. Because offrequent problems in the field such as stirring and casting it is necessary to use the additive (additive) that Sikament LN as the concrete mix in order to mix more encer.Sehinggaadukannya facilitate stirring and casting, reducing loss and speeding up the hardening of concrete (concrete early strength. Year First researching matrieal be used. Second yeardesigning the concrete mix using the red brand white cement with added material SikamentLN. Third-year result compressive strength, slump values, the levels of each of theingredients (water, cement, aggregates, SikamentLN)in the mix.Research by the addition ofa dditive Sikament LNt ersebut targeted obtain data on compressive strength of normalconcrete using red and white brand cement and additives plus Sikament LNat 28 days. Keywords: compressive strength of concrete, the slump value of the concrete, the concretemaker ingredient content